SHEAR BOND STRENGTH OF CHAIRSIDE CAD-CAM BLOCKS TO ERODED DENTIN - Elif Aydoğan Ayaz; Tuğba Serin Kalay; Pınar Naiboğlu (Cumhuriyet University, 2022)
Objectives: To assess the shear bond strength (SBS) of chairside computer-aided design and computer-aided manufacturing (CAD-CAM) blocks to dentin subjected to simulated gastric erosion when cemented with self-etch and self-adhesive resin cements. Materials and Methods: One hundred eighty dentin samples were assigned to two groups: sound and eroded dentin. In the eroded dentin group, samples were eroded with HCl (0.01 M, pH 2, 2 min) and stored in artificial saliva for 60 min then, brushed using a power brush (2N, 15 s). This cycle was repeated three times. CAD-CAM blocks (3x3x3 mm3, n=15/group) of Lava Ultimate (LU), Vita Enamic (VE), and Vita Suprinity (VS) were cemented to sound and eroded dentin with self-etch Multilink N (MN) and self-adhesive RelyX U200 Automix (RU) resin cements. SBS was measured after 24 hours. The failure mode was assessed by using a stereomicroscope. Data was analyzed with 3-way ANOVA and Bonferroni correction (p˂0.05). Results: The SBS was significantly affected by the main factors: tooth structure (p=0.011), resin cements (p˂0.001), and CAD-CAM blocks (p=0.001). When LU was cemented with RU to sound dentin, a higher SBS was obtained compared to eroded dentin (p=0.001). MN revealed significantly higher SBS than RU (p